Rodents: A Bane to Agriculture - Chaudhary, Vipin (Indian Journal of Plant Protection, 2025)
Rodents form a highly diverse group of mammals, with over 2,000 species worldwide. However, only a relatively small percentage, approximately 10%, are recognized as agricultural nuisances. These rodents pose a significant threat in both agricultural and commensal settings, consistently undermining our efforts to enhance food supplies for a growing global population. They inflict substantial damages and economic losses across the entire food production cycle, including cultivation, transportation, and storage. Accurately quantifying the precise losses incurred in agricultural production due to rodent activity is challenging due to the multifaceted nature of their direct and indirect harm, as well as variations in the intensity and speed of infestation. A comprehensive analysis of available data on rodent-induced damage and economic losses within the country reveals persistent chronic damage ranging from 2% to 15% across various sectors. Moreover, severe damage occasionally leads to a complete loss of field crops. Rodents are known for their prolific breeding habits, characterized by a short oestrus cycle lasting 3 to 7 days, a brief gestation period of approximately three weeks, and the potential to produce large litters of up to 20 offspring per female. The available options for rodent control can be categorized into two fundamental approaches: the lethal or reductional approach and the non-lethal or preventive approach. The lethal approach, which primarily involves the use of rodenticides, offers an immediate solution to the problem and is often regarded as the most practical, cost-effective, and efficient means of addressing rodent issues. In contrast, non-lethal or preventive measures encompass environmental, cultural, and biological methods, which have the potential to yield longer-lasting effects but are less frequently adopted. Due to variations in geographical and climatic factors, crop production and storage systems, the carrying capacity of the environment, the biology of the pest rodent species, the nature and extent of rodent problems, and the perceptions and socioeconomic conditions of the people, no single strategy or method of control is universally applicable in different pest situations. However, for the sustainable management of pest rodents, it is imperative to integrate alternative strategies rooted in crops/cropping systems, ecology, and the behavior of these pests.